Language Features Used to Describe Major Character in Short Stories - Eka Puspita; Azwandi Azwandi; Irma Diani (Universitas Bengkulu, 2018)
Language Features are the important aspect in a text. This is part of the student’s knowledge. If the students familiar with the language features, they can understand the major characters in the texts easily. The purpose of this study is to analyze the language features that used to describe major characters in short stories. This research was a descriptive qualitative research. The research objects were taken at six Indonesian short stories and six English short stories. The research procedure classifies all objects based on language features of research instruments.The results of this study are there are two characters of major character in the short stories, protagonist and antagonist. In Indonesian short stories there are two short stories that have antagonist characters and four short stories have protagonist characters. And all of the short stories only have one major character. But in English short stories, four of the short stories have two major characters and two short stories only have one major character.Keywords: Language Features, Short Stories, Characters, Major Characters